The Efforts to improve student learning outcomes in analyzing the preparation of planting materials through a cooperative model of the type of think pair and share (TPS) in class X SMK N 10 Bungo: Upaya Meningkatkan Hasil Belajar Siswa Pada Materi Menganalisis Penyiapan Bahan Tanam Melalui Model Kooperatif Tipe Think Pair And Share (TPS) Di Kelas X SMK N 10 Bungo - Yasril (Perkumpulan Doktor Indonesia Maju (PDIM), 2021)
This research is motivated by the low learning outcomes of class X students in Analyzing the Preparation of Planting Materials where many students have not reached the KKM 75. The low student learning outcomes are due to many students who still do not develop their thinking and are still less active in the learning process. In addition, during the learning process, the teacher interacted less with students and only asked students to take notes on the material provided. In addition, the applied model is still not oriented to varied learning. Therefore, this Classroom Action research aims to improve student learning outcomes in the classroom.